2003
DOI: 10.1021/la035557h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Poly(acrylic acid) Block Length Distribution on Polystyrene-b-poly(acrylic acid) Block Copolymer Aggregates in Solution. 2. A Partial Phase Diagram

Abstract: The first paper of the series, which focused on the effect of polydispersity on the self-assembly of block copolymer vesicles, showed that an increase in the width of the poly(acrylic acid) (PAA) block length distribution resulted in a decrease in the size of the vesicles formed. In this paper, the rest of the phase diagram is explored. For the present study, a series of polystyrene-b-poly(acrylic acid) copolymers of an identical polystyrene length of 325 units but of varying degrees of polymerization of PAA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 40 publications
3
107
0
Order By: Relevance
“…In addition, the micelle clusters or large compound micelles may also cause the size from the DLS to be larger than that from the TEM, because the TEM result is only a partial reflection of the micelle size. A similar result is also reported by Eisenberg and co-workers [24]. In their study on the self-assembly of polystyrene-block-poly(acrylic acid) (PS-b-PAA), both the DLS and TEM results show a very broad distribution size range of the spherical micelles as large compound micelles are formed.…”
Section: Core-shell Micelles Of Ps-b-p4vpsupporting
confidence: 87%
“…In addition, the micelle clusters or large compound micelles may also cause the size from the DLS to be larger than that from the TEM, because the TEM result is only a partial reflection of the micelle size. A similar result is also reported by Eisenberg and co-workers [24]. In their study on the self-assembly of polystyrene-block-poly(acrylic acid) (PS-b-PAA), both the DLS and TEM results show a very broad distribution size range of the spherical micelles as large compound micelles are formed.…”
Section: Core-shell Micelles Of Ps-b-p4vpsupporting
confidence: 87%
“…At first it was speculated that polymer vesicles were non-equilibrium structures because of the glassy nature of the PS membrane, but their thermodynamic stability was subsequently established. [37][38][39][40] Further work confirmed that vesicular morphologies are not dictated by the kinetically frozen glassy nature of the hydrophobic block, since vesicles could be formed with low glass transition temperature (T g ) hydrophobes such as PBD [41,42] and poly(propylene oxide) (PPO). [43] Since these initial reports, there have been hundreds of papers that describe the formation of polymer vesicles and a number of excellent reviews.…”
Section: Block Copolymer Vesiclesmentioning
confidence: 87%
“…This phenomenon is a particularity of the self-assembly of amphiphilic block copolymers even though it may occur also for pegylated phospholipids, having a macromolecular polar head. Moreover, Eisenberg et al demonstrated, by blending a series of PS-b-PAA block copolymer presenting similar PS molecular weight but variable PAA molecular weight, that vesicle size tends to decrease when the polymolecularity of the hydrophilic chains increases, due to this segregation phenomenon that tends to increase the membrane curvature [30,31]. Interestingly the vesicle size polydispersity has also been reported to decrease in the meantime, leading to this counter-intuitive result that more polydisperse chains lead to more mono-disperse assemblies!…”
Section: Control Of the Polymersome Sizementioning
confidence: 99%